Prediction of Malaysian Talus Bone Morphology Using Artificial Intelligence - Rosdi, Daud; Nurazlina, Sulaeman; Mas Ayu, Hassan; Arman Shah, Abdullah (Springer Science and Business Media Deutschland GmbH, 2022)
Book cover pp 29–37Cite as